ChemInform Abstract: A General Pd‐Catalyzed α‐ and γ‐Benzylation of Aldehydes for the Formation of Quaternary Centers. Issue 41 (October 2015) - Franzoni, Ivan; Guenee, Laure; Mazet, Clement
Abstract Using benzyl methyl carbonates as substrate, a series of α‐branched aldehydes is benzylated.